THE EFFECT OF PLAYING METHODS ON INCREASING PENCAK SILAT CRESCENT KICK SPEED IN FIFTH-GRADE STUDENTS AT MI MUHAMMADIYAH MUNTUKDAWUNG - Aan Ashaddin Anhar; Ahmad Syarif (Journal of Social and Economics Research, 2026)
This study aims to determine the effect of playing methods on increasing the speed of sickle kicks in student learning at school. The study used a quantitative approach with a one-group pretest-posttest experiment design. The population and sample of the study amounted to 44 students selected using a total sampling technique. The instrument used was a sickle kick speed test to a punching bag target within 10 seconds. Data analysis was carried out through normality tests, homogeneity tests, and hypothesis testing using paired sample t-tests. The results showed that the playing method had a significant effect on increasing the speed of sickle kicks in grade V students of MI MUTU Rowokele. This increase was seen from changes in test results which were initially dominated by the sufficient, less, and very less categories, then increased to be dominated by the good and very good categories after being given treatment. The results of the hypothesis test showed a significance value of p <0.005, which indicated a significant difference. These findings indicate that the application of the playing method can be an effective learning alternative to improve students' motor skills.